2000
DOI: 10.1037/0021-9010.85.4.612
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability in the workplace: Development of a taxonomy of adaptive performance.

Abstract: The purpose of this research was to develop a taxonomy of adaptive job performance and examine the implications of this taxonomy for understanding, predicting, and training adaptive behavior in work settings. Two studies were conducted to address this issue. In Study 1, over 1,000 critical incidents from 21 different jobs were content analyzed to identify an 8-dimension taxonomy of adaptive performance. Study 2 reports the development and administration of an instrument, the Job Adaptability Inventory, that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
1,201
8
55

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,141 publications
(1,379 citation statements)
references
References 31 publications
25
1,201
8
55
Order By: Relevance
“…Recently, for example, Pulakos et al (2000) suggested an addition to previous descriptions of job performance in the area of adaptability. Using content analysis techniques, Pulakos et al examined critical incidents of job performance to create a taxonomy of adaptive job performance.…”
Section: Current Models Of Job Performancementioning
confidence: 99%
See 3 more Smart Citations
“…Recently, for example, Pulakos et al (2000) suggested an addition to previous descriptions of job performance in the area of adaptability. Using content analysis techniques, Pulakos et al examined critical incidents of job performance to create a taxonomy of adaptive job performance.…”
Section: Current Models Of Job Performancementioning
confidence: 99%
“…Just as the work of Pulakos et al (2000) begins to meet the growing need to understand and enhance adaptability in organizations, the development of a taxonomy of interpersonal performance will provide a fi-amework to understand and enhance employees' abilities to interact effectively with others and use their social environments to facilitate organizational goal attainment.…”
Section: Current Models Of Job Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Using this task vs. non-task behavioral categorization, other subsets of work behavior can be readily classified within one of these categories. For example, adaptive performance (Hesketh & Neal, 1999;Pulakos, Arad, Donovan, & Plamondon, 2000) and proactive work behavior (Crant, 2000;Frese & Fay, 2001;Parker, Williams, & Turner, DYNAMIC JOB SATISFACTION SHIFTS 241 2006) exemplify forms of task behavior, as they directly relate to task completion. In contrast, workplace behavior related to managing the work-family interface-referred to as family-supportive supervisor behavior-can be described as a type of non-task behavior.…”
Section: Dynamic Job Satisfaction Shifts 240mentioning
confidence: 99%